Pulmonary arteriovenous aneurysm - Larre Borges, Uruguay; Chiossoni, M; Filgueira, José L (Cirugía del Uruguay, 2021)
The paper presents the procedure for establishing diagnosis and treatment to be applied in a case of pulmonary arteriovenous aneurism.